Early intervention and long‐term outcome with cardiac resynchronization therapy in patients without a history of advanced heart failure symptoms. (29th April 2015) - Herscovici, Romana; Kutyifa, Valentina; Barsheshet, Alon; Solomon, Scott; McNitt, Scott; Polonsky, Bronislava; Lee, Andy Y.; Zareba, Wojciech; Moss, Arthur J.; Goldenberg, Ilan
<x xml:space="preserve">Abstract</x> Aims MADIT‐CRT showed that cardiac resynchronization therapy with a defibrillator (CRT‐D) improves long‐term outcomes in currently mildly symptomatic heart failure (HF) patients with LBBB regardless of the presence of prior advanced HF symptoms. We aimed to evaluate the long‐term benefit of CRT‐D in patients who never experienced advanced HF symptoms prior to device implantation. Methods and results Interaction term analysis was used to compare the clinical and echocardiographic benefit of CRT‐D vs. implantable cardioverter defibrillator (ICD)‐only therapy during long‐term follow‐up (median 5.6 years) between LBBB patients with or without a history of advanced HF [defined as NYHA class ≥ III or past hospitalization for worsening HF >3 months prior to enrolment in MADIT‐CRT (n = 529 and 752, respectively)]. Multivariable analysis showed that treatment with CRT‐D was associated with a significant reduction in the risk of HF or death during long‐term follow‐up regardless of the presence of prior advanced HF symptoms [hazard ratio 0.53 (P < 0.001) and 0.47 (P < 0.001) in the respective groups of patients with and without prior advanced HF; interaction P for the difference = 0.58]. Echocardiographic response to CRT at 1 year was also similar between the two groups (P > 0.10 for all comparisons). Conclusion Our findings suggest that treatment with CRT‐D is associated with pronounced echocardiographic and long‐term clinical benefit in patients with LV dysfunction and LBBB who never experienced advanced HF symptoms. These data further emphasize the benefit of early intervention with CRT in this population.